2015
DOI: 10.1051/0004-6361/201526262
|View full text |Cite
|
Sign up to set email alerts
|

B fields in OB stars (BOB): FORS 2 spectropolarimetric follow-up of the two rare rigidly rotating magnetosphere stars HD 23478 and HD 345439

Abstract: Aims. Massive B-type stars with strong magnetic fields and fast rotation are very rare and pose a mystery for theories of star formation and magnetic field evolution. Only two such stars, called σ Ori E analogues, were known until recently. A team involved in APOGEE, one of the Sloan Digital Sky Survey III programs, announced the discovery of two additional rigidly rotating magnetosphere stars, HD 23478 and HD 345439. The magnetic fields in these newly discovered σ Ori E analogues have not been investigated so… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 20 publications
3
35
0
Order By: Relevance
“…The line presents a central absorption component and line-wing emissions on both sides of the Hα line extending up to approximately ±300 km s −1 . The presence of similar Hα emission wings has been reported for other strongly magnetic He-strong stars, such as HD 23478 ( B z = 1.5 kG; Hubrig et al 2015) and HD 37479 (σ Ori E, B z = 2.4 kG; Oksala et al 2012), for example. Despite the similarities between the He-strong stars CPD −62 • 2124 and CPD −57 • 3509, the latter does not show any spectral feature indicative of circumstellar material (see Fig.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The line presents a central absorption component and line-wing emissions on both sides of the Hα line extending up to approximately ±300 km s −1 . The presence of similar Hα emission wings has been reported for other strongly magnetic He-strong stars, such as HD 23478 ( B z = 1.5 kG; Hubrig et al 2015) and HD 37479 (σ Ori E, B z = 2.4 kG; Oksala et al 2012), for example. Despite the similarities between the He-strong stars CPD −62 • 2124 and CPD −57 • 3509, the latter does not show any spectral feature indicative of circumstellar material (see Fig.…”
Section: Discussionsupporting
confidence: 82%
“…Landstreet & Borra 1978;Borra & Landstreet 1979;Bohlender 1988;Bagnulo et al 2006;Hubrig et al 2015), pointing out Hestrong stars as a sub-class of strong magnetic early B-type stars. Within the context of the "B fields in OB stars" (BOB) collaboration (Morel et al 2014(Morel et al , 2015Hubrig et al 2014aHubrig et al , 2015Fossati et al 2015b;Schöller et al 2017), here we report the detection of an exceptionally strong magnetic field in the He-strong B2IV star CPD −62 • 2124 (V = 11.04 mag ;Drilling 1981;Walborn 1983;Zboril et al 1997;Renson & Manfroid 2009). The star was observed using two different instruments (Sect.…”
Section: Introductionmentioning
confidence: 99%
“…Evolutionary tracks of Brott et al (2011) for initial rotational velocity of ∼300 km s −1 are shown (full lines), labelled by initial stellar mass. The magnetic star in the Trifid nebula and HD 345439 (Hubrig et al 2014(Hubrig et al , 2015b are not included here because of difficulties in establishing their properties. (Lotkin & Matkin 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Some material may also be trapped in a centrifugal magnetosphere (see e.g. Petit et al 2013;Hubrig et al 2015b), giving rise to "doublehorned" line profiles in Hα and some near-IR hydrogen lines that are characteristic of the σ Ori E analogues. The He-strong nature of CPD −57 • 3509 was first noticed by Evans et al (2005, designated as NGC 3293-034) in a systematic spectroscopic survey of the massive star content of the open cluster NGC 3293.…”
Section: Introductionmentioning
confidence: 99%
“…The prototype of a rigidly rotating magnetosphere (RRM) is σ Ori E (Groote & Hunger 1997;Townsend, Owocki & Groote 2005). Evidence of circumstellar matter bound to the strong stellar magnetic field has been reported in a few other cases (Leone et al 2010;Bohlender & Monin 2011;Grunhut et al 2012a;Rivinius et al 2013;Hubrig et al 2015;Sikora et al 2015).…”
Section: Introductionmentioning
confidence: 99%